Estimation of viscosity for some silicate slags - Shu, Qifeng; Wang, Lijun; Chou, Kuochih (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
A new method combining KTH model with geometrical model (General solution model by Chou) to estimate viscosity of slags was proposed in this work. According to modified KTH model, viscous Gibbs free energy for mixing of ternary slags was estimated by employing general solution model. It was found that viscous Gibbs energy for mixing of ternary system or higher order system could be calculated using solely viscous Gibbs energy for mixing of sub-binary systems. Viscosities of five ternary slags CaO-MnO-SiO2, CaO-FeO-SiO2, FeO-MnO-SiO2 , CaO-MgO-SiO2 and FeO-MgO-SiO2 were estimated in the present work. A good agreement with mean deviation being less than 20% was achieved. The modified KTH model has advantages with less model parameters and improved estimation ability by comparison to original KTH model.